2014
DOI: 10.5194/acp-14-6345-2014
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Manitou Experimental Forest Observatory: site description and selected science results from 2008 to 2013

Abstract: The Bio-hydro-atmosphere interactions of Energy, Aerosols, Carbon, H2O, Organics & Nitrogen (BEACHON) project seeks to understand the feedbacks and inter-relationships between hydrology, biogenic emissions, carbon assimilation, aerosol properties, clouds and associated feedbacks within water-limited ecosystems. The Manitou Experimental Forest Observatory (MEFO) was established in 2008 by the National Center for Atmospheric Research to address many of the BEACHON research objectives, and it now provides a fixed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 93 publications
(117 reference statements)
5
114
1
Order By: Relevance
“…The exception to this finding is the case of the large discrepancy of 23% between the FMPS and SMPS when the SMPS LDMA WCPC in high sample flow mode when comparing data at the original discretization of the five systems. The discrepancy in estimation of GMD and σ g (and total number concentrations) between different SMPS configurations may have importance to studies where: (i) batteries of SMPS systems are used to sample different segments of the PNSD (Ortega et al 2014), (ii) different SMPS or CPC systems are used to calibrate aerosol mass spectrometers (Laitinen et al 2009), or (iii) where growth rates for ultrafine particles or PNSD are compared between studies that employed different SMPS and/or FMPS systems (Pryor et al 2011;Yli-Juuti et al 2011). With respect to the latter, Laitinen et al (2009) indicated median uncertainties in growth rates from 7 to 20 nm, from three different instruments (differential mobility particle sizer, a balanced scanning mobility analyzer and an air ion spectrometer) due to their differential sensitivity to particles of different sizes, of only 8%, but our data suggest the GR uncertainty from 20-50 nm deriving from use of FMPS versus SMPS may be considerably more.…”
Section: Discussionmentioning
confidence: 99%
“…The exception to this finding is the case of the large discrepancy of 23% between the FMPS and SMPS when the SMPS LDMA WCPC in high sample flow mode when comparing data at the original discretization of the five systems. The discrepancy in estimation of GMD and σ g (and total number concentrations) between different SMPS configurations may have importance to studies where: (i) batteries of SMPS systems are used to sample different segments of the PNSD (Ortega et al 2014), (ii) different SMPS or CPC systems are used to calibrate aerosol mass spectrometers (Laitinen et al 2009), or (iii) where growth rates for ultrafine particles or PNSD are compared between studies that employed different SMPS and/or FMPS systems (Pryor et al 2011;Yli-Juuti et al 2011). With respect to the latter, Laitinen et al (2009) indicated median uncertainties in growth rates from 7 to 20 nm, from three different instruments (differential mobility particle sizer, a balanced scanning mobility analyzer and an air ion spectrometer) due to their differential sensitivity to particles of different sizes, of only 8%, but our data suggest the GR uncertainty from 20-50 nm deriving from use of FMPS versus SMPS may be considerably more.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprene concentrations are calculated in this study using that approximation, which gives values typically < 300 ppt. While largely dominated by biogenic emissions, the site receives some airflow from the front range urban areas (Denver metropolitan area and Colorado Springs) on most days, as evidenced by moderate increases in NO x , CO, and anthropogenic VOCs during late afternoon and into the evening (Fry et al, 2013;Ortega et al, 2014;Chan et al, 2016).…”
Section: Beachon-rombas Campaignmentioning
confidence: 99%
“…It was a collaboration of 27 institutions from the United States and Europe, focused on understanding primary and secondary biogenic aerosol emissions, formation, and processing. An overview of atmospheric chemistry research at the Manitou Experimental Forest Observatory, including the BEACHON-RoMBAS campaign, has been previously published (Ortega et al, 2014).…”
Section: Beachon-rombas Campaignmentioning
confidence: 99%
“…These included conventionally and organically cropped land and pasture at the University of Wyoming's Sustainable Agricultural Research and Extension Center (SAREC), near Lingle, Wyoming, sagebrush shrubland, native glacial scree grassland and lodgepole pine forest in south-east Wyoming, and ponderosa pine forest at the Manitou Experimental Forest Observatory (MEFO) (Ortega et al, 2014) in Colorado. Details of sites and vegetation are given in Table 1.…”
Section: Soil Samplingmentioning
confidence: 99%